Risk of Early Childhood Caries Estimated by Maternal Dental Caries during Pregnancy: A Retrospective Cohort Study - Thearawiboon, Sunithi; Rojanaworarit, Chanapong (European Journal of Dentistry, 2024)
Objective Public policy promoting prenatal dental care to provide long-term prevention of early childhood caries (ECC) in offspring would require evidence regarding the ECC risk associated with maternal dental caries during pregnancy. This study evaluated that association using a design capable of assessing temporal relationships and considered a directed acyclic graph to guide the adjustment of pertinent confounders.Materials and Methods This retrospective cohort study analyzed data from 158 mother–child dyads attending care at Prachathipat Hospital, Pathum Thani, Thailand. Maternal dental caries data at their first visits to prenatal oral care from February 2012 to May 2017 were traced forwardly to match the oral health data of offspring who visited the hospital from May 2013 to March 2018.Results Univariable and multivariable fractional logit regression models along with the calculation of average marginal effects revealed that children born to two categories of mothers with 1 to 5 and ≥6 carious teeth during pregnancy would averagely develop 4.5 to 5 and 7.9 to 8.8 more carious teeth per 100 teeth than dental caries would occur in offspring of caries-free mothers.Conclusion This evidence identified the role of maternal dental caries during pregnancy as a significant clinical risk indicator for ECC and supported the provision of prenatal dental care for mothers to prevent ECC in offspring.
Keywords: dental caries; risk indicator; pediatric dentistry; epidemiology